Effect of Organic Cations on Hydrogen Oxidation Reaction of Carbon Supported Platinum. Issue 14 (1st January 2016) - Chung, Hoon Taek; Choe, Yoong-Kee; Martinez, Ulises; Dumont, Joseph H.; Mohanty, Angela; Bae, Chulsung; Matanovic, Ivana; Kim, Yu Seung
Abstract : Effect of organic cations on hydrogen oxidation reaction (HOR) of carbon supported platinum (Pt/C) is investigated using three 0.1 M alkaline electrolytes, tetramethylammonium hydroxide (TMAOH), tetrabutylammonium hydroxide (TBAOH) and tetrabutylphosphonium hydroxide (TBPOH). Rotating disk electrode experiments indicate that the HOR of Pt/C is adversely impacted by time-dependent and potential-driven chemisorption of organic cations. In-situ infrared reflection adsorption spectroscopy experiments indicated that the specific chemisorption of organic cations drives the hydroxide co-adsorption on Pt surface. The co-adsorption of TMA + and hydroxide at 0.1 V vs. reversible hydrogen electrode is the strongest; consequently, complete removal of the co-adsorbed layer from Pt surface is difficult even after exposure the Pt surface to 1.2 V. Conversely, the chemisorption of TBP + is the weakest, yet notable decrease of HOR current density is still observed. The adsorption energies, ΔE, for TMA +, TBA +, and TBP + on Pt (111) surface from density functional theory are computed to be −2.79, −2.42 and −2.00 eV, respectively. The relatively low adsorption energy of TBP + is explained by the steric hindrance and electronic effect. This study emphasizes the importance of cationic group on HOR activity of alkaline anion exchange membrane fuel cells.